Phototrophic Colonization in Dolomitic Limestone: Comparison between Single vs Artificial Multispecies - Soares, Fabiana (2023)
Phototrophic organisms, such as microalgae and cyanobacteria, are known to be major contributors to stone decay. The purpose of this study was to assess the dolomitic limestone colonization by phototrophic organisms, using single vs artificial multispecies, under laboratory conditions. To achieve this aim, dolomitic limestone blocks were inoculated with single phototrophic species previously collected from the Old Cathedral of Coimbra, for a period of threemonths. In parallel, limestone blocks were also inoculated with a mixture of the same isolated single species, in order to compare the colonization capacities of both conditions. Results were evaluated based on visual inspection, surface covered area, colorimetric and SEM analyses. Results showed that the phototrophic organisms were able to colonize the dolomitic limestone blocks in both conditions (single vs artificial multispecies), but biofilm development was more enhanced when single species, rather than multispecies, were used. The obtained results also allowed to observe the capacity for endolithic colonization and the formation of small cavities by some species.